BaTa2V2O11: A novel low fired microwave dielectric ceramic. Issue 13 (November 2015) - Fang, Liang; Guo, Huanhuan; Fang, Weishuang; Wei, Zhenhai; Li, Chunchun
Abstract: A Ta-containing microwave dielectric ceramic BaTa2 V2 O11 with rhombohedral structure was prepared using the conventional solid-state reaction method. Dense BaTa2 V2 O11 ceramic was obtained at relatively low sintering temperatures (∼870 °C). The ceramic exhibited a high quality factor value ( Q × f) of 41, 958 GHz, a moderate relative permittivity of 28.2, and a temperature coefficient of the resonant frequency ( τ f ) of 91 ppm/°C. The large positive τ f of BaTa2 V2 O11 could be compensated by forming composite ceramics with Ba2 BiV3 O11, and 0.4BaTa2 V2 O11 –0.6Ba2 BiV3 O11 ceramic exhibited improved microwave dielectric properties with ɛ r ∼21.1, Q × f ∼44, 760 GHz and τ f ∼1.9 ppm/°C. The low sintering temperature and favorable microwave dielectric properties make 0.4BaTa2 V2 O11 –0.6Ba2 BiV3 O11 as a potential candidate material for high-frequency applications.